Risk Factor Analysis of Dengue Fever in Makassar City using the Simple Additive Weighting Method - Paseleng, Fatricius; Susetyo, Yeremia Alfa (Sistemasi: Jurnal Sistem Informasi, 2025)
Dengue Fever is caused by the Flavivirus, which is transmitted through the bites of Aedes aegypti mosquitoes and several other Aedes species. Dengue Fever has a significant impact on public health, especially in large cities like Makassar. This study employs the Simple Additive Weighting (SAW) method to evaluate the main risk factors for dengue fever in Makassar City. The research will be conducted through several stages, including literature review, data collection, determining criteria and their weights, normalizing the decision matrix, calculating final scores, and making decisions. The results indicate that the Totaka sub-district has the highest dengue risk with a score of (0.395307), followed by Gusung (0.329353), while Barang Caddi has the lowest dengue risk (0.000618). This study aims to provide a ranking of dengue risks that can assist decision-makers in formulating prevention and control strategies for dengue fever in Makassar City.